Ocorrência do SNP c.767G>T no gene DNM1responsável pelo colapso induzido pelo exercício em cães da raça Labrador Retriever no Estado de São Paulo - Basso, Roberta M. [UNESP] (2015)
The exercise-induced collapse (EIC) is considered an autosomal recessive syndrome that mainly affects Labrador Retriever dogs. The disease is characterized by muscle weakness and collapse after intense exercise. Recovery usually occurs after exercise but some animals may die. The clinical signs occurs due to the single-nucleotide polymorphism (SNP) c.767G>T in Dynamin 1 (DNM1) gene. The aim of this study was to evaluate the occurrence of this SNP in 321 Labrador Retriever dogs from Sao Paulo state. Specific primers for amplification of the entire exon 6 of the DNM1 gene were used in a PCR performed with DNA from blood or buccal swab samples, direct sequencing was performed for the final evaluation. Among 321 animals studied, 3.4% (11/321) of animals were homozygous for the DNM1 SNP (c.767G>T) and 24.6% (79/321) were heterozygous. Only one of the 11 homozygous animals in this study had previous clinical signs compatible with this disease. This is the first study that evaluated the occurrence of DNM1 SNP (c.767G>T) gene in Brazil and considering that almost 25% of the studied animals were heterozygous, the routinely evaluation of this SNP may be important before this breed mating The EIC should be include in the differential diagnosis of neuromuscular diseases in Labrador Retriever dogs.